THE ISSUE OF STUDYING THE HISTORY WORLD WAR II - Mukhayyo Isakova (Galaxy International Interdisciplinary Research Journal, 2022)
Dozens of dissertations have been defended by domestic researchers, hundreds of books and a significant number of scientific articles have been written, highlighting the participation and contribution of the Uzbek people to the victory over fascism. Nevertheless, there are a number of topics that require careful study of new materials and the development of balanced conclusions. In particular, when describing the heroic deeds of the Uzbek soldiers, we should not forget about those who, at the cost of their lives, by the will of fate, were captured by the enemy. At the same time, the researcher must take into account all the circumstances related to the degree of their education, physical fitness, armament, ability and skills to use military equipment, etc. In the article, based on the study of official reports, statistical materials and memoirs of the participants in the war, the author argues that the main contingent of those taken prisoner were victims of Soviet social policy, young conscripts 17-19 years old, poorly trained, did not undergo military physical training and poorly armed soldiers fighting against the professional German army..